2012
DOI: 10.1159/000342719
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Renal Failure in Patients with Lupus Nephritis: Data from the Spanish Registry of Glomerulonephritis

Abstract: Background: Lupus nephritis (LN) is a severe complication of systemic lupus erythematosus. Data from national registries based on renal biopsies are scarce. The aim of our study was to analyze the demographic characteristics, clinicopathological correlations, and risk factors associated with renal failure in patients with LN at the time of renal biopsy. Methods: We performed a cross-sectional observational study based on data from the Spanish Registry of Glomerulonephritis for the years 1994–2009. The outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
2
12
2
2
Order By: Relevance
“…In multivariants survival analysis, we found that SBP, Scr, hypocomplementemia, severe proliferative lesion (LN IV or VI) and SLEDAI score are independent indicators of poor renal outcome in LN patients. Our findings were somewhat different to those reported [10,15,16]. Although hypocomplementemia and SLEDAI score are commonly assumed as indicators of active lupus [17], our study is the first one that identifies them as independent risk factor for poor renal outcome.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In multivariants survival analysis, we found that SBP, Scr, hypocomplementemia, severe proliferative lesion (LN IV or VI) and SLEDAI score are independent indicators of poor renal outcome in LN patients. Our findings were somewhat different to those reported [10,15,16]. Although hypocomplementemia and SLEDAI score are commonly assumed as indicators of active lupus [17], our study is the first one that identifies them as independent risk factor for poor renal outcome.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the opinion that outcome of LN was related to renal pathological lesions, only few studies were performed to clarify this hypothesis [9,10]. In this study, we found that disease severity and organ damage in LN II were mild.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…However, in the same study initial elevation of serum creatinine concentration did not influence the prognosis. 12 Initial heavy proteinuria or even nephrotic syndrome did not have bearing on ultimate prognosis in our series. The levels of serum creatinine on the other hand were found to affect prognosis.…”
Section: Discussionmentioning
confidence: 49%
“…12,[17][18][19] Of these the Chronicity index and its components have been more consistently found to correlate with long term prognosis. 20 In our study Chronicity indices and two of its componentstubular dilatation and interstitial fibrosis were found to be significant.…”
Section: Discussionmentioning
confidence: 99%